Factors influencing the preparedness for the implementation of the national health insurance scheme at a selected hospital in Gauteng Province, South Africa - Ntsibeng Valerie Mukwena; Zodwa Margaret Manyisa (BMC, 2022)
Abstract Research studies as well as anecdotal evidence suggest that there are challenges regarding the NHI plan implementation. These include problems such as an increase in illnesses and a shortage of personnel to drive the project in South African public hospitals. This is exacerbated by the existing situation of most government-funded healthcare institutions, which are characterized by bad administration, insufficient budget, inadequate infrastructure, and insufficient drug supply, as highlighted in several studies. The hospital under investigation is one such facility, with a history of patients sleeping on the floor and people being turned away owing to a shortage of experts and an overburdened staff. This situation is concerning, given that the government claims to be providing appropriate funds to the institution. The hospital under research is highly regarded by the surrounding community. However, a visit by the Health MEC in 2014 revealed that the facility had insufficient sanitary standards and a high complaint rate. Based on the foregoing, as well as the difficulties that both employees and patients are confronted with at the  selected hospital, the question that emerges is whether the hospital is fit for the implementation of the NHI. Aim: The aim of this study was to assess the preparation for the launch of the national health insurance scheme at a Johannesburg hospital. Setting: The study was conducted at a hospital situated in eastern suburbs of Johannesburg, Gauteng, South Africa. Method: The study employed a qualitative method with an explorative, descriptive, qualitative study design. The population consisted of selected hospital employees, such as doctors, dispensary officers, hospital managers, human resources workers, facility managers, and administration record officials who were employed at the selected hospital. Purposive sampling was used to select participants. Sample size: Category saturation was used to determine the sample size. The participants for the study were chosen using purposeful sampling, with the researcher aiming for those who were familiar with the NHI scheme at the institution. Semi structured interviews and a focus group discussion were used to gather data. The data from the focus group discussion and semi-structured interviews were analysed using thematic analysis. Results: The investigation found that the hospital was preparing to for the NHI implementation, but that was riddled with lack of resources, poor infrastructure, lack of training, delays in development and poor technological advances. Recommendations: The paper suggests that human resources be increased, infrastructure be upgraded, medicines and equipment be increased, and enough training on NHI implementation be provided. Contribution: The paper adds to the body of knowledge regarding the NHI in South Africa.